Hambatan bagi Shanghai Cooperation Organization untuk Membuka Jalan Menuju Supranasionalisme - Mahbi Maulaya (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2021)
Considering that the Shanghai Cooperation Organization (SCO) successfully brings forth intensive cooperation and prompts great intimacy among its members, many states perceive SCO as a promising regional organization for bridging their interests and shouldering their burden. Consequently, participation within SCO has expanded with the arrival of several new members and participants. Having in mind that its notoriety grown by leaps and bounds, can SCO increase its capability and competence as a regional organization by becoming a supranational one? Can SCO input supranationalism norms and values into its mechanism? This study argues that it is futile for us to expect that SCO possesses supranational capacity. The argument derives from the fact that SCO is the agent designed to safeguard its member’s sovereignty, and it consists of stubborn hegemonic power with bold nationalism. This study generated the aforementioned assessment by addressing the idea of supranationalism and implementing qualitative research and library research method.